2017
DOI: 10.1523/eneuro.0028-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Suprachiasmatic Nucleus Interaction with the Arcuate Nucleus; Essential for Organizing Physiological Rhythms

Abstract: The suprachiasmatic nucleus (SCN) is generally considered the master clock, independently driving all circadian rhythms. We recently demonstrated the SCN receives metabolic and cardiovascular feedback adeptly altering its neuronal activity. In the present study, we show that microcuts effectively removing SCN-arcuate nucleus (ARC) interconnectivity in Wistar rats result in a loss of rhythmicity in locomotor activity, corticosterone levels, and body temperature in constant dark (DD) conditions. Elimination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…Surgical micro-cuts that eliminate these reciprocal connections lead to arrhythmicity in locomotor activities, corticosterone levels, and body temperature in the constant darkness condition in rats. Interestingly, the SCN clock gene rhythmicity was not altered by these micro-cuts while the ARC gene rhythmicity was disrupted (Buijs et al, 2017). These findings suggest that the autonomous clock in the SCN controls the molecular clock in the ARC and potentially other brain regions through a complex neuronal projection network.…”
Section: Neural Anatomy Of the Central Circadian Clockmentioning
confidence: 99%
“…Surgical micro-cuts that eliminate these reciprocal connections lead to arrhythmicity in locomotor activities, corticosterone levels, and body temperature in the constant darkness condition in rats. Interestingly, the SCN clock gene rhythmicity was not altered by these micro-cuts while the ARC gene rhythmicity was disrupted (Buijs et al, 2017). These findings suggest that the autonomous clock in the SCN controls the molecular clock in the ARC and potentially other brain regions through a complex neuronal projection network.…”
Section: Neural Anatomy Of the Central Circadian Clockmentioning
confidence: 99%
“…This finding suggested that abnormal clock gene rhythms or reduced coordination among rhythms might contribute to impairments in sleep–wake rhythms and cognition in AD patients. Because the SCN controls the phase of clock gene rhythms throughout the brain and body (Abraham, Prior, Granados‐Fuentes, Piwnica‐Worms, & Herzog, ; Buijs et al., ; Granados‐Fuentes, Prolo, Abraham, & Herzog, ; Yoo et al., ), the desynchrony of clock gene rhythms in extra‐SCN regions in the AD brain might result from deficits in SCN function. Alternatively, other factors might induce or contribute to attenuation or desynchrony of clock gene rhythms in extra‐SCN regions.…”
Section: Molecular Basis Of Circadian Rhythms and Alterations During mentioning
confidence: 99%
“…Genetic disruption of the SCN clock does not completely eliminate rhythmic dopamine release in the ARC indicating a semi‐autonomous clock machinery . Nevertheless, cutting the connections between ARC and the SCN results in desynchronization of the former . Hypothalamic regions are important control centres of many rhythmic physiological functions.…”
Section: Brain Clocks Outside the Scnmentioning
confidence: 99%
“…Rhythmic clock gene expression in neuroendocrine dopaminergic neurons of the ARC suggested that prolactin secretion might be under the control of the ARC oscillator . Interestingly, rats with ablated SCN‐ARC connections show arrhythmic GC levels, body temperature and locomotor activity in DD suggest a close interaction in SCN and ARC clocks in the regulation of these outputs . Guzmán‐Ruiz et al reported that the balance of α‐MSH release from the ARC together with arginine vasopressin neurons from the SCN is fundamental for the daily body temperature rhythm through projections to the MPN .…”
Section: Functional Studies Of Extra‐scn Oscillatorsmentioning
confidence: 99%